Pengaruh Faktor Individual terhadap Pengambilan Keputusan Etis Konsultan Pajak - Anita Fitriyani; Maria Augustine Graciafernandy (Jurnal Ilmiah Aset, 2023)
Currently, tax consultant services are increasing and play a very important role in facilitating taxpayers to comply with their tax obligations. Tax consultants must be able to make decisions for taxpayers in carrying out their obligations in accordance with existing regulations as taxpayers. This study was conducted in a tax consulting firm located in Semarang City, where the influence of individual factors on ethical decision making in a tax consulting firm was investigated. The method of analysis used in this study is the quantitative method of analysis. The variables in this study use the independent variables, i.e., ethics and social responsibility, machiavellianism, ethical consideration, and professional commitment, while the dependent variable is ethical decision-making. The population of this study is tax advisors in the city of Semarang. The population of this study is based on IKPI Semarang.The population of tax consultants in Semarang as of November 2022 is 273 people. Sample selection using purposive sampling method. Based on the criteria, 100 respondents who were consultants in the city of Semarang were obtained as samples in this study. The results of this study indicate that ethics and social responsibility, Machiavellianism, ethical considerations, and professional commitment simultaneously influence ethical decision making.